A prospective observational study involving three fixed infusion regimens of phenylephrine for hemodynamic support during spinal anaesthesia for caesarian delivery - Masood, Aymen; Rasool, Ajaiz; Mir, Aabid Hussain; Neesa, Waqurl; Farooqi, Ayaz (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Spinal anaesthesia used in caesarian section is associated with hypotension which can have maternal and fetal side effects. To determine the efficacy and ideal dosing of Phenylephrine in attenuating the hypotensive episodes during caesarean section under spinal anaesthesia. Methods: 100 patients were allocated to four groups, placebo group (PE 0) and 3 fixed phenylephrine infusion regimens, phenylephrine 25 μg/min-1 (PE 25), phenylephrine 50 μg/min-1 (PE 50), and phenylephrine 75 μg/min-1 (PE 75). Blood pressure, heart rate were noted among primary variables and fetal parameters like umbilical blood pH and lactate were recorded as secondary parameters. Results: There was a significant reduction in heart rate with increasing the infusion dosage of phenylephrine, with a mean of 86.8 beats/min at the end of procedure in placebo group and 69.4 beats/min in 75 μg group (p value <0.001). There was significant statistical difference among systolic blood pressure in the four groups after 7 min of the procedure and p-value of <0.05 with better attenuation of hypotension in infusion groups as compared to placebo. Similarly there was significant statistical difference in diastolic blood pressure among the four groups after 8 min of the procedure with p values <0.05. Conclusions: Prophylactic phenylephrine infusions reduced the incidence and severity of maternal pre-delivery hypotension. Among the fixed rate phenylephrine infusion regimens investigated, infusion rates of 50 μg/min-1 were associated with greater maternal hemodynamic stability compared with 25 and 75 μg/min-1, with minimal side effects and intervention.